Improving project success : A case study using benefits and project management - Gomes, Jorge (2022)
In the face of rapid technological changes, short product cycles and strong global competition, it is vital that organizations know how to optimize their scarce resources and thus profit from investments with the goal of obtaining the expected benefits and successes. One of the great difficulties facing organizations is the large number of projects that they usually have in their portfolio. Therefore, it is necessary to select and prioritize which projects become essential, to guarantee the maximum return on investments and the sustainability of the organization. Although there are several approaches to analyzing and selecting projects, there is no unanimity about which methodologies to apply. When analyzed in more detail, all approaches presented advantages and disadvantages which need to be considered. Project selection also depends on the nature and profile of the managers and on the techniques, that best fit the organization’s environment. This study analyzes and establishes the link between the academic literature and a pilot model of selection and prioritization of projects developed by the Portuguese Navy. The project was carried out to improve the support and allocation of the necessary resources and forces for the accomplishment of the Navy’s missions in the context of Portugal’s National Defense. The results obtained ensure the necessary alignment with the academic literature and reinforces the credibility of the proposal model for the selection and prioritization process. .